Community resident and sustainable cultural heritage tourism development: a systematic literature review using PRISMA - Yanying, Liu; Subramaniam, Thanam; Konar, Rupam; Fuchs, Kevin; Kunasekaran, Puvaneswaran; Ragavan, Neethiahnanthan Ari (Institute for Tourism, 2026)
Residents are key stakeholders in sustainable tourism development and play an essential role in tourism growth. While previous studies have explored residents' support for tourism from economic and environmental perspectives, the unique relationship between cultural heritage preservation and community empowerment has not been sufficiently explored. Cultural heritage tourism naturally generates conflicts between commodification and preservation, yet current frameworks often overlook residents' cultural identity and empowerment as crucial factors for sustainable outcomes. This omission is particularly significant in the post-pandemic recovery context, where heritage sites face increased risks of over-tourism and community marginalization. To address this gap, the study conducted a systematic literature review of 53 articles published through January 2025. Using the PRISMA methodology, it identified relevant theories and examined direct, mediating, and moderating factors. Additionally, this research developed a conceptual framework to support the sustainable development of cultural heritage tourism, offering new insights and guiding future studies. The findings provide valuable knowledge for tourism researchers, destination managers, and policymakers, while the framework serves as a practical tool for destinations seeking to balance tourism growth with heritage preservation and community well-being.